2020
DOI: 10.1080/07391102.2020.1761881
|View full text |Cite
|
Sign up to set email alerts
|

Natural products may interfere with SARS-CoV-2 attachment to the host cell

Abstract: SARS-CoV-2 has been emerged in December 2019 in China, causing deadly (5% mortality) pandemic pneumonia, termed COVID-19. More than one host-cell receptor is reported to be recognized by the viral spike protein, among them is the cell-surface Heat Shock Protein A5 (HSPA5), also termed GRP78 or BiP. Upon viral infection, HSPA5 is upregulated, then translocating to the cell membrane where it is subjected to be recognized by the SARS-CoV-2 spike. In this study, some natural product compounds are tested against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
145
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(148 citation statements)
references
References 51 publications
0
145
0
3
Order By: Relevance
“…Interestingly, we found that coffee extracts exhibited in vitro efficacy against SARS-CoV-2. While modelling studies suggested that ingredients in coffee such as chlorogenic acid, caffeic acid, and tannins show activity against SARS-CoV-2, 23 we here provide in vitro evidence of such an effect. Future studies are needed to elucidate the effect of coffee and active ingredients on SARS-CoV-2 in detail.…”
Section: Discussionmentioning
confidence: 53%
“…Interestingly, we found that coffee extracts exhibited in vitro efficacy against SARS-CoV-2. While modelling studies suggested that ingredients in coffee such as chlorogenic acid, caffeic acid, and tannins show activity against SARS-CoV-2, 23 we here provide in vitro evidence of such an effect. Future studies are needed to elucidate the effect of coffee and active ingredients on SARS-CoV-2 in detail.…”
Section: Discussionmentioning
confidence: 53%
“…When infected, HSPA5 is upregulated and translocated to the cell membrane where it is recognized by the SARS-CoV-2 spike to drive the infection process. Elfiky et al (Elfiky, 2020) have tested several compounds from natural product against the HSPA5 substratebinding domain b (SBDb) by molecular docking and molecular dynamics simulations. The phytoestrogens (Daidzin, Genistein, Formononetin, and Biochanin A) and estrogens have proximal binding affinities with HSPA5.…”
Section: Natural Products Inhibiting Sars-cov-2mentioning
confidence: 99%
“…Withaferin A, Withanolide D, Enoxacin, Mercaptopurine and Aloe-emodin are tested against various target proteins of viruses (Muralidharan et al, 2020). Conversely, various phytochemicals reported in the literature to possess potential antiviral activity that could be an alternative to restrict the coronavirus replication (Elfiky, 2020). Natural compounds consist of high chemical diversity, lower cost of production than that of biotechnological products or compounds synthesised from combinatorial chemistry and also possess milder or inexistent side effects than chemical drugs (Kitazato et al, 2007).…”
Section: Introductionmentioning
confidence: 99%